The Influence of Green Marketing Environmentally Friendly Bags on Green Behavior of Modern Mini-market Retail Consumers in Yogyakarta - Evi Rosalina Widyayanti; Titik Desi Harsoyo (Relevance: Journal of Management and Business, 2023)
Damage to the environment and ecosystem can be caused by various things, one of which is the accumulation of residual waste or waste originating from industry and households. Plastic bag waste has become a common problem across continents and countries, waterways and oceans. Plastic bag waste is increasing in Indonesia every year and the environmental conditions are very concerning. The use of eco-friendly shopping bags needs to be encouraged to reduce the use of plastic bags. Starting in 2009, several supermarkets or supermarkets and hypermarkets in Indonesia have started to promote eco-friendly campaigns, namely the use of eco-friendly cloth shopping bags (green bags) as a substitute for plastic bags which tend not to be environmentally friendly. Therefore it is important for consumers to contribute to environmental sustainability through pro-environmental behavior (pro-environment).